The interplay between herbal medicines and gut microbiota in metabolic diseases - Wang, Lijie; Gou, Xiaoling; Ding, Yin; Liu, Jingye; Wang, Yue; Wang, Yaqian; Zhang, Jing; Du, Leilei; Peng, Wei; Fan, Gang (Frontiers in Pharmacology, 2023)
Metabolic diseases are becoming a major public health problem worldwide. Herbal medicines are medicinal materials or preparations derived from plants, which are widely used in the treatment of metabolic diseases due to their good curative effect and less side effects. Recent studies have shown that gut microbiota plays an important role in the herbal treatment of metabolic diseases. However, the mechanisms involved are still not fully understood. This review provides a timely and comprehensive summary of the interactions between herbal medicines and gut microbiota in metabolic diseases. The mechanisms by which herbal medicines treat metabolic diseases include their effects on gut microbial composition, intestinal barrier, inflammation, and microbial metabolites (e.g., short-chain fatty acids and bile acids). They can increase the abundance of beneficial bacteria (e.g., Akkermansia and Blautia), reduce the abundance of harmful bacteria (e.g., Escherichia-Shigella), protect the intestinal barrier and alleviate inflammation. In turn, gut microbes can metabolize herbal compounds, thereby increasing their bioavailability and bioactivity, as well as reducing toxicity. These findings suggest that the therapeutic effects of herbal medicines on metabolic diseases are closely related to their interactions with gut microbiota. In addition, some methods and techniques for studying the bi-directional interaction between herbal medicines and gut microbiota are proposed and discussed. The information presented in this review will help us to better understand the therapeutic mechanisms of herbal medicines and the key role of gut microbiota in them.